Demand planning for vaccinations using the example of seasonal influenza vaccination - country comparison and implications for Germany - Anna Bußmann; Christian Speckemeier; Pauline Schlesiger; Jürgen Wasem; Isabelle Bekeredjian-Ding; Bernhard Ultsch (BMC Public Health)
Abstract Background Annual vaccination is the most important measure to prevent influenza infection. However, demand planning of influenza vaccines is challenging due to seasonal adaptations of virus strains and long production times. The aim was to analyze how other countries manage the demand planning of seasonal influenza vaccines and to draw implications for the German demand planning system for seasonal (influenza) vaccines. Methods A two-stage approach has been adopted. As a first step, an analysis of the German demand planning system was carried out to identify key challenges. Second, an analysis of comparable countries with regard to solution strategies was conducted. For this, six comparator countries were selected based on different healthcare systems and structures (Australia, Canada, Great Britain, Singapore, Switzerland, USA). Targeted searches in PubMed, Google Scholar and on websites of agencies and organizations were performed. Further information was requested through e-mail correspondence with the ministries of health and other relevant institutions. In addition, experts from the pharmaceutical industry in the selected countries were approached via written survey. Results Identified challenges in the demand planning of influenza vaccines in Germany include a lack of reliability of the current demand planning system, bureaucratic burden, lack of binding orders, financial liability of GPs, vaccine discard and limited possibilities of reordering. Various approaches have been identified in six comparator countries. Some of them are already implemented in the German system, others could address the challenges in the German demand planning for influenza vaccines. These include vaccine forecast methods, monitoring systems/vaccination registers, a central platform for orders, (earlier) preorders, centralized purchase system, reimbursement of a surplus and reallocation and return systems. The different approaches are discussed and linked to address the challenges of the German system. Conclusions Several approaches have been identified that may be suitable to address the challenges of the German system of (influenza) vaccine demand planning. In the future, further investigation is necessary to assess the potential feasibility and implementation on a health policy level.